Sexual Predation and TEFL : The Teaching of English as a Foreign Language Enables Sexual Predation - Rapatahana, Vaughan, (Critical New Literacies: The Praxis of English Language Teaching and Learning ;, 2025)
Teaching English as a Foreign Language (TEFL) enables sexual predation across the wide range of activities and locales it encompasses, beyond schools and inclusive of voluntourist and aid programmes where EFL is taught. This predation is carried out not only by male Native-speaking English Teachers (NETs) on their students, peers, and members of local communities but also carried out on female NETs and EFL students by locals. Is TEFL inherently sexist, utilising gender-biased texts? This book is the first to examine in considerable detail such English language sexual imperialism and to suggest ways to curtail it. See Less